Human Fatality Due to Thallium Poisoning: Autopsy, Microscopy, and Mass Spectrometry Assays1, 2. Issue 1 (18th November 2014) - Li, Shangxun; Huang, Wen; Duan, Yijie; Xing, Jingjun; Zhou, Yiwu
Abstract Thallium has been responsible for many intoxications since its discovery; however, toxicological profiles for thallium in human fatalities have not been updated recently. Autopsy, microscopic investigations, and toxicological analyses were performed on a married couple who died from thallium sulfate intended homicidal poisoning. The distribution of thallium was established by inductively coupled plasma mass spectrometry with hair samples showing the highest thallium concentration. Electron microscopy revealed a dystrophic condition of hair with disorganized cuticle and atrophy of the hair bulb. Thallium interacts with cells at different levels, with prominent ultrastructural injuries in the mitochondria and endoplasmic reticulum, and high concentration of electron dense granules observed in the cytoplasm and mitochondria of several organs. Alopecia, toxic encephalopathy, and peripheral neuropathy were diagnosed in the victims and suggested to be crucial implications for thallium poisoning. The analytical procedures used in this case are of considerable forensic importance in the diagnosis of thallium poisoning.